Translational Oncology - Multiplex Diagnosis of Oncogenic Fusion and MET Exon Skipping by Molecular Counting Using Formalin-Fixed Paraffin Embedded Lung Adenocarcinoma Tissues. Issue 2 (February 2016) - Sunami, Kuniko; Furuta, Koh; Tsuta, Koji; Sasada, Shinji; Izumo, Takehiro; Nakaoku, Takashi; Shimada, Yoko; Saito, Motonobu; Nokihara, Hiroshi; Watanabe, Shun‐ichi; Ohe, Yuichiro; Kohno, Takashi
ABSTRACT: : Introduction: : Fusions of the anaplastic lymphoma receptor tyrosine kinase gene ( ALK ), ret proto‐oncogene (RET ), ROS proto‐oncogene 1, receptor tyrosine kinase gene ( ROS1 ), B‐Raf proto‐oncogene, serine/threonine kinase gene (BRAF ), and neuregulin 1 gene ( NRG1 ) and intronic MMNG HOS Transforming gene ( MET ) mutations are druggable oncogene alterations in lung adenocarcinoma that cause expression of aberrant transcripts. Because these aberrant transcripts are both infrequent (incidence <5%) and mutually exclusive, multiplex assays are required to detect them in tumor samples. Methods: : Aberrant transcripts of the six aforementioned oncogenes (36 transcripts in total) were examined in a molecular counting (MC) assay, which counts RNA molecules by simultaneous hybridization of several probes. Forty‐one samples of surgically resected lung adenocarcinoma tissue found to express one of these aberrant oncogenic transcripts upon whole transcriptome sequencing (test cohort: n = 22) or reverse transcription polymerase chain reaction (validation cohort: n = 19) analyses were subjected to MC, after which biopsies were performed on tumor tissue samples. Results: : Threshold values for the diagnosis of each of the 36 transcripts were determined in frozen and formalin‐fixed paraffin‐embedded samples from the test cohort. On the basis of these threshold values, the MC assay diagnosed expression of oncogenic transcripts in the validation cohort samples with 100% accuracy. The assay also accurately detected oncogenic fusions in bronchial lavage fluid and transbronchial biopsy samples. Conclusions: : The MC assay allows multiplex detection of oncogenic fusion and exon‐skipped transcripts in tumor samples, including in formalin‐fixed paraffin‐embedded samples obtained in the clinic.